Behavioral and Physiological Symptoms of Dementia (BPSD): A Literature Review - Larasati, Anak Agung Ayu Regina; Nuriasti, Rovera; Febriana, Nanggi Qoriatul; Dwiandika, Rizki Ary; Mahardika, Agustine (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Dementia is a progressive syndrome characterized by cognitive decline, impacting daily functioning. Behavioral and Psychological Symptoms of Dementia (BPSD), including sleep disturbances, hallucinations, delusions, apathy, depression, and agitation, are prevalent in over 90% of patients, further exacerbating their quality of life and increasing caregiver burden. This research aims to evaluate the effectiveness of both pharmacological and non-pharmacological interventions in managing BPSD, focusing on non-pharmacological methods such as cognitive therapy and social stimulation. Data was collected through a comprehensive review of recent studies, analyzing interventions and their outcomes in reducing BPSD symptoms. The findings reveal that non-pharmacological approaches are more effective in reducing agitation and depression, with cognitive therapy showing up to 75% effectiveness. In contrast, pharmacological treatments, though useful for acute symptoms, offer limited long-term benefits. The research underscores the need for integrated, evidence-based approaches, combining medical and psychosocial support to improve patient care and alleviate caregiver stress. These findings suggest the importance of adopting holistic management strategies, particularly those that reduce isolation and enhance social interaction, in the long-term care of dementia patients.